Word Problem Strategy for Latino English Language Learners at Risk for Math Disabilities. (February 2014) - Orosco, Michael J.
English Language Learners (ELLs) at risk for math disabilities (MD) are challenged in solving word problems for numerous reasons such as (a) learning English as a second language, (b) limited experience using math vocabulary, and (c) lack of strategies to improve word-problem-solving skills. As a result of these difficulties, ELLs may not only need math support but also oral language and reading development assistance. The purpose of this study was to assess the effectiveness of a math comprehension strategy procedure based on a dynamic assessment (DA) framework. The strategy provided scaffolding support based on the student's reading and language comprehension levels. A multiple baseline was used to assess 6 third-grade Latino ELLs at risk for MD. As compared with baseline, the strategy increased problem-solving ability for all participants. All students' level of performance was maintained during follow-up sessions. Results suggest that a focus on comprehension strategies may help facilitate math skills development for ELLs at risk for MD.